2019
DOI: 10.4314/jab.v133i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of somatic embryos of recalcitrant genotypes of <i>Theobroma cacao L.</i>

Abstract: Objective: In cocoa tree (Theobroma cacao L.), some elite genotypes have shown, in standard study conditions, an absence or a very weak response to induction of somatic embryos. This is the case of the original C8 genotype Trinidad. This study aims to improve the production of somatic embryos in this genotype Methodology and results: To do this, staminodes and petals excised from immature buds of genotypes C1, C8 and C14 were used. Genotypes C1 and C14 are embryogenic under standard conditions. These floral ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…According to their reports, T. cacao flower bud explants yield high percentages of callus during cocoa somatic embryogenesis. Our results show a success that could also be explained by the nutrient composition of the culture medium and the effect of the hormonal balance used (Daouda et al, 2019;Osorio Montoya et al, 2022). The hormonal balance (2,4-D / TDZ) used in the culture medium is the best condition to obtain callus (Boutchouang et al, 2016).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…According to their reports, T. cacao flower bud explants yield high percentages of callus during cocoa somatic embryogenesis. Our results show a success that could also be explained by the nutrient composition of the culture medium and the effect of the hormonal balance used (Daouda et al, 2019;Osorio Montoya et al, 2022). The hormonal balance (2,4-D / TDZ) used in the culture medium is the best condition to obtain callus (Boutchouang et al, 2016).…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, there is an early production of embryos by the C1, C9, C14, and C16 genotypes between the 2nd and 4th weeks in the EDM medium, and a late production of embryos by the C8 genotype between the 12 and 16 th weeks in the EDM medium. These results may be linked to the plant gene, which has an immediate impact on the recalcitrance of certain tissues and genotypes concerning their totipotency (Daouda et al, 2019). Prolonged subculture on the EDM medium of T. cacao is, therefore, necessary to overcome recalcitrance or improve the response of certain genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Some elite genotypes of cacao showed a low or an absence response to somatic embryogenesis induction (Daouda et al 2019). also reported that the frequency of PSE in nine Indonesian cacao genotypes is varied between 0-67%.…”
Section: Effect Of Explant Types and Pgrs Compositions On Secondary S...mentioning
confidence: 93%
“…Recalcitrance of certain important fruit crops such as Theobroma cacao means a barrier in plant regeneration of plants using somatic embryogenesis, where the high composition of phenols inhibits this process. Furthermore, somatic embryogenesis is a genotype-dependent process that requires development and optimisation of new protocols to overcome this limitation (Pancaningtyas, 2015;Henao et al, 2018;Koné et al, 2019;Pérez-Caselles et al, 2021).…”
Section: Transformation Of Cocoa Leaves Mediated By Agrobacteriummentioning
confidence: 99%